Recent N-Atom Containing Compounds from Indo-Pacific Invertebrates - Ashgan Bishara; Maurice Aknin; Yoel Kashman (Marine Drugs, 2010)
A large variety of unique N-atom containing compounds (alkaloids) without terrestrial counterparts, have been isolated from marine invertebrates, mainly sponges and ascidians. Many of these compounds display interesting biological activities. In this report we present studies on nitrogenous compounds, isolated by our group during the last few years, from Indo-Pacific sponges, one ascidian and one gorgonian. The major part of the review deals with metabolites from the Madagascar sponge Fascaplysinopsis sp., namely, four groups of secondary metabolites, the salarins, tulearins, taumycins and tausalarins.